Recent advances in gut microbiota and thyroid disease: pathogenesis and therapeutics in autoimmune, neoplastic, and nodular conditions - Fang, Lihua; Ning, Jie (Frontiers in Cellular and Infection Microbiology, 2024)
This review synthesizes key findings from the past five years of experimental literature, elucidating the gut microbiome’s significant influence on the pathogenesis of thyroid diseases. A pronounced shift in the gut microbiota composition has been consistently observed, with a significant reduction in bacteria such as Bifidobacterium, Bacillaceae, Megamonas, and Clostridium, and a notable increase in bacteria, including Bacteroides, Proteobacteria, Actinobacteria, Desulfobacterota, and Klebsiella. These alterations are implicated in the development and progression of thyroid diseases by impacting metabolic pathways including bile acid and cytokine production, including a decrease in short-chain fatty acids (SCFAs) that are crucial for immune regulation and thyroid hormone homeostasis. The review also highlights the therapeutic implications of probiotics in managing thyroid conditions. Evidence suggests that probiotic adjunct therapy can modulate the gut microbiota, leading to improvements in thyroid function and patient outcomes. The use of specific probiotic strains, such as Lactiplantibacillus plantarum 299v and Bifidobacterium longum, has demonstrated potential in enhancing the effects of traditional treatments and possibly restoring a balanced gut microbiota. Notably, fecal microbiota transplantation (FMT) has emerged as a promising intervention in Graves’ Disease (GD), demonstrating the potential to recalibrate the gut microbiota, thereby influencing neurotransmitters and trace elements via the gut-brain and gut-thyroid axes. The integration of microbiome-based therapies with traditional treatments is anticipated to usher in a new era of personalized thyroid disease management, offering a more nuanced approach to patient care. By integrating this body of work, the review offers an innovative perspective on the gut microbiome’s broad impact on thyroid diseases and the therapeutic applications of probiotics.